Application of NAA and BA to Calotropis gigantea (L.) W.T. Aiton in vitro - Muji Rahayu; Tyas Alivia Wulandari; Amalia Tetrani Sakya; Andriyana Setyawati; Sri Hartati; Samanhudi Samanhudi (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2023)
Crown flower (Calotropis gigantea (L.)) is a weed plant potentially to be used as raw material for textile fibers yet the utilization is not optimal. Efforts to optimize the utilization of C. gigantea are needed. This research aimed to determine the appropriate concentration of plant growth regulators, including NAA (Naphthalene Acetic Acid) and BA (Benzyl Adenine) to stimulate optimal growth of C. gigantea to be used as the basis for in vitro propagation of C. gigantea. The research was arranged in a completely randomized design (CRD). Explants were planted on Murashige and Skoog (MS) medium with various concentrations of NAA (0; 0.5; 1; 1.5; and 2 ppm) and BA (0; 1; 2; 3; and 4 ppm). Based on the research result, the addition of 3 ppm BA followed by increasing the concentration of NAA to 1.5 ppm could increase the number of C. gigantea shoots, and giving 1 ppm BA followed by adding 1.5 to 2 ppm NAA increased shoot height. The best plantlet response was found in media with 0 ppm NAA and 4 ppm BA, which could produce an optimal shoot height of 5.9 cm and a large number of shoots of 5.67 shoots. Increasing NAA concentration retarded root formation and reduced the root length and number of leaves, while the medium without NAA gave the earliest root emergence of 11 days after planting, the number of leaves of 20 strands, and the longest root of 10.9 cm. Applying a single substance BA did not accelerate all the variables observed.